Vegetation on rock outcrops in the Serra do Sincorá, Chapada Diamantina, Bahia, Brazil - Neves, Sâmia Paula Santos; Conceição, Abel Augusto (SITIENTIBUS série Ciências Biológicas, 2007)
The Chapada Diamantina, which represents the northern portion of the Espinhaço Range, is characterized by a mosaic of caatinga and cerrado vegetation, diverse forests types, and principally “campos rupestres”. Its flora is rich in characteristic species, including many endemics. Vegetation of the Chapada Diamantina has been heavily altered by several anthropogenic factors making its conservation urgent. This work was designed to aid in the elaboration of a management plan for the Chapada Diamantina National Park. It deals with the floristic composition and structural aspects of vegetation growing on rock outcrops situated between 400-500 m a.s.l. Four areas (12º35’S and 41º23’W) with a high proportion of exposed rock surface were chosen for detailed examination, and four 10 x 10 m plots were randomly selected for floristic sampling in each of these exposed areas. Each of the four 10 x 10 m plots was further subdivided into 25 2 x 2 m subplots in order to estimate species coverage. We found 57 species of vascular plants distributed among 27 families, including eight monocotyledons, 18 eudicotyledons and one monilophyte. Although the eudicotyledons had the highest numbers of species, the monocotyledons demonstrated the highest coverage. The most abundant species was Vellozia punctulata Seub., which mainly occurred in dense stands. The rock outcrops studied demonstrate similarities with the “campos rupestres”, in terms of the richest families, the most abundant species, and life forms (hemicryptophytes, nanophanerophytes and chamaephytes). Similarity analysis between the 10 x 10 m plots demonstrated groups related to the numbers of species present.